P05.52 The phenomenon of pseudoprogression in diffuse astrocytic and oligodendroglial tumors (grade II-III),treated with photon beam radiotherapy and temozolamide. Report of a single institution - Fotopoulou, E (Neuro Oncol, 2018)
BACKGROUND: Pseudoprogressive disease (PsPD) after brain tumor treatment is a phenomenon that affects overall approach of patients in an uncertain way. Radiologically pseudoprogression is defined as emerging or enlarging area(s) of contrast agent enhancement, without measurable tumor growth, which diminishes or stabilizes without alterations to treatment schedule. THE AIM: of the study is to report the incidence of radiological proven pseudoprogression in grade II-III diffuse astrocytic and oligodendroglial tumors after treatment of radiation therapy and temozolamide in our department and the impact on treatment strategy MATERIAL AND METHODS: Between 2009 and 2017 seventeen patients age >18 years with grade II-III diffuse astrocytic and oligodendroglial tumors (histologically proven) were treated with photon beam (3D-conformal) radiation therapy and temozolamide. Clinical and imaging (MRI) data were reviewed. Among them 9 patients had anaplastic astrocytoma grade III, 3 patients anaplastic oligodendroglioma grade III, 3 patients with oligodendroglioma grade II, 2 patients with grade II diffuse gliomas. Pseudoprogression was defined as a new enhancing lesion occurring after RT and subsequently disappearing or remaining stable for at least one year without therapy, or dexamethasone. RESULTS: All patients received RT and temozolamide. The prescribed dose was 60Gy with 2Gy per/fraction for high grade gliomas (grade III) and 45-54Gy with 2Gy per/fraction for low grade gliomas (grade II). The median follow-up was 4 years (range 1‒9 y). Among patients, three patients (17.6%) presented pseudoprogression (two with anaplastic astrocytoma and one with anaplastic oligodendroglioma) and received no other oncological treatment or medication(dexamethasone) until proof of progressive disease. PsPD always occurred within the PTV that received 60G. CONCLUSION: In our cohort pseudo progression was observed among a small percentage of patients with grade III diffuse astrocytic and oligodendroglial tumors but not among patients with grade II tumors. The decision of new line treatment was postponed until conclusive evidence of progressive disease.